Emerging Tick-Borne Viruses in the Twenty-First Century - Mansfield, Karen L.; Jizhou, Lv; Phipps, L. Paul; Johnson, Nicholas (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks, as a group, are second only to mosquitoes as vectors of pathogens to humans and are the primary vector for pathogens of livestock, companion animals, and wildlife. The role of ticks in the transmission of viruses has been known for over 100 years and yet new pathogenic viruses are still being detected and known viruses are continually spreading to new geographic locations. Partly as a result of their novelty, tick-virus interactions are at an early stage in understanding. For some viruses, even the principal tick-vector is not known. It is likely that tick-borne viruses will continue to emerge and challenge public and veterinary health long into the twenty-first century. However, studies focusing on tick saliva, a critical component of tick feeding, virus transmission, and a target for control of ticks and tick-borne diseases, point toward solutions to emerging viruses. The aim of this review is to describe some currently emerging tick-borne diseases, their causative viruses, and to discuss research on virus-tick interactions. Through focus on this area, future protein targets for intervention and vaccine development may be identified.